Kajian Dinamika Kelompok Tani Dalam Peningkatan Pendapatan Kecamatan Tomohon Timur Kota Tomohon - Supit, Veky; Rantung, Ventje; Pakasi, Caroline (JURNAL ILMIAH SOCIETY, 2016)
farmer Group, basically, is a non-formal organization of village that grows and develops â€œFrom, by and to farmerâ€ which have some characteristics of to know, to intimate and to trust each other. One of the basic goal that already there in all society of Indonesia is the spirit of mutual cooperation in development. The spirit of mutual cooperation pictured in activities of group of society, known as mutual assistence. The mutual assistence system in the development of village can be seen from the farmer groups as the potential organization in the agriculture Result of the initiative activities, creativity and even real action can be seen through group which has had more than one unit of trade, which dynamically can influence the income of society of farmer groups.. But, we also need to suggest the goverment to improve the agriculture technology and to prepare istitutions or economic enterprise in this case cooperation that would able to accomodate all productionsÂ  so that the market price can be controlled. Key words : farmer group and farmer group dynamic